State Government Communication Strategy in Disseminating Development Information in Kaitetu, Central Maluku - Fatmawati Rumra; Yuniar Sakinah Waliulu (Publikasi Indonesia, 2024)
Communication is a process that aims to spread or convey a number of meaningful messages, both between individuals, groups and organizations. Remembering that basically every individual has the desire to speak, to convey his ideas and opinions and obtain all information. So, then it gives rise to a communication process. Some time ago in conveying a number of messages, they usually used simple tools such as kentongan, the sound of a whistle, which became a symbol of communication. This research aims to get an overview of government development communication and media literacy in conveying a number of messages to cause understanding and change in people's behavior. The end of the purpose of this research is to give birth to a development communication role model that makes more use of all communication media that are increasingly developing and can be used as a reference. The following are important points of the purpose of this research is to find an effective development communication process. This study uses a descriptive qualitative method. The type of data in this study uses the type of qualitative data, the main source of data in qualitative research The type of data in this study uses the type of qualitative data, the main source of data in qualitative research includes ideas, expressions and views of the informants on development communication in the delivery of a number of messages. The selection of informants in this study is by using the purposive sampling method. The informant in this study is the staff of the Central Maluku Kaitetu State Government. This study found that the Kaitetu State Government in disseminating development information determines a number of communication strategies, namely planning, setting goals and objectives, forming messages, selecting media or media choices and eval_uation.